-96+5x=-8x+86

Simple and best practice solution for -96+5x=-8x+86 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -96+5x=-8x+86 equation:


Simplifying
-96 + 5x = -8x + 86

Reorder the terms:
-96 + 5x = 86 + -8x

Solving
-96 + 5x = 86 + -8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8x' to each side of the equation.
-96 + 5x + 8x = 86 + -8x + 8x

Combine like terms: 5x + 8x = 13x
-96 + 13x = 86 + -8x + 8x

Combine like terms: -8x + 8x = 0
-96 + 13x = 86 + 0
-96 + 13x = 86

Add '96' to each side of the equation.
-96 + 96 + 13x = 86 + 96

Combine like terms: -96 + 96 = 0
0 + 13x = 86 + 96
13x = 86 + 96

Combine like terms: 86 + 96 = 182
13x = 182

Divide each side by '13'.
x = 14

Simplifying
x = 14

See similar equations:

| 2x+2=x+56 | | -3n-4=-2-3n | | 12x+14y=112 | | D-8d+7= | | 5x+2-x=2(x+3) | | 5(3x+2)-4+2(-5x+4)-3+14+2(5x-1)-7(3x+2y)+5(4x+2y)+11(5x+3y)+4(12x+5y)= | | 28=(4+x)+x | | 178-5x=40x+18 | | 9-x=x | | 2(x-4)+4x=10 | | -x+-3=7 | | .75v-6=.75v-6 | | 2x2=3 | | 6(c+9)=5c-1 | | 4=0.33(b+2) | | 7(x-1)+5=6-8x+7 | | 5x+3x=7x+2 | | 9x-5=3x-59 | | 21+2=24 | | 6x+9y=72 | | 4(y-9)=(y+21) | | 5(x-6)=9(2x+1) | | 6x+9=4x+13 | | 4x-(2x-3)=14 | | 0.6(x+100)+0.4x=85 | | 4s+2s-6=6 | | 7x+18=-2(x-18) | | -11/20=x-13/16 | | -11=14+x | | 4x+3=22x | | 2x-13=8-6x+3 | | 2(4x+3)=5(3x+4) |

Equations solver categories